MITIGASI BENCANA TSUNAMI MELALUI PARIWISATA (Studi Kasus di Situs Tsunami Kapal PLTD Apung Banda Aceh) - Muhammad Bilal Habibie; Saleh Sjafie; Khairuddin . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
Aceh is a vulnerable area of natural disasters, then, mitigation disaster must be improved to prevent collateral damage of the disaster. The study upon disaster managements: planning, organizing, human resource recruitment, leadership, and supervising, on one of educational and tourism site in Banda Aceh, PLTD Apung, became the object of this study. This site was selected since it was projected as a site for disaster mitigation, particularly for earthquake and Tsunami. The data were collected by observation, interview, and document recording toward relating parties including manager and staffs of the site, the heard of tourism board of Banda Aceh, tourist guides, people nearby, and visitors. The result indicated that the government had planned the establishment of priority zone for disaster mitigation along with socialization and relating policies. The organization disaster mitigation included pre-disaster preparation, rescue, and recovery post-disaster. Then, the recruitment of involved staffs also involved the training of mitigation management. Then, the ministry of human resource along with local government had established several policies on disaster management. Then, informants also admitted that disaster management conveyed disaster mitigation and early warning system.